Annual Bluegrass Biology and Management in Turf - Darcy E. Partridge-Telenko; Barry J. Brecke; J. Bryan Unruh; Ramon Leon (EDIS)
This is part of the Weed Biology and Management in Turf series by J. Bryan Unruh, Darcy E. Partridge-Telenko, Barry J. Brecke, and Ramon Leon that highlights key facts about each weed, and include herbicide options for each variety of Florida turfgrass. Published by the UF Department of Environmental Horticulture, July 2009. 2009 version unavailable, February 2013 and April 2016 revisions included instead.